Monetary transmission right from the start: The (dis)connection between the money market and the ECB's main refinancing rates - Puriya Abbassi; Dieter Nautz (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2010)
The relation between the ECB's main refinancing (MRO) rates and the money market is key for the monetary transmission process in the euro area. This paper investigates how money market rates respond to the new information revealed by MRO auctions. Our results confirm a stabilizing level relationship between the overnight rate Eonia and MRO rates before the financial crisis. Since the start of the financial crisis, however, we find that MRO auction outcomes even exacerbated the disconnection of money market rates from the policy-intended interest rate level. These findings support the fixed rate full allotment policy introduced by the ECB as an unconventionalmeasure to re-stabilize banks' refinancing conditions.
Keywords: E43; E52; E58; D44; 330; Financial Crisis; Monetary transmission process; Central bank auctions; European Central Bank; Money markets; Refinanzierung; Geldpolitik; Geldmarkt; Zinspolitik; Offenmarktpolitik; Zins; Transmissionsmechanismus; Finanzmarktkrise; EU-Staaten